Effect of red blood cell transfusion on short-term outcomes in very low birth weight infants - Eui Young Lee; Sung Shin Kim; Ga Young Park; Sun Hyang Lee (The Korean Pediatric Society, 2020)
Background Red blood cell (RBC) transfusion improves cardiorespiratory status of preterm infants by increasing circulating hemoglobin, improving tissue oxygenation, and reducing cardiac output. However, RBC transfusion itself has also been suggested to negatively affect short-term outcomes such as intraventricular hemorrhage (IVH), bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), and necrotizing enterocolitis (NEC) in premature infants. Purpose This study aimed to analyze the relationship between RBC transfusion and short-term outcomes in very low birth weight (VLBW) infants (birth weight, <1,500 g). Methods We retrospectively reviewed the medical records of VLBW infants admitted to the Soonchunhyang University Bucheon Hospital between October 2010 and December 2017. Infants who died during hospitalization were excluded. The infants were divided into 2 groups according to RBC transfusion status. We investigated the relationship between RBC transfusion and short-term outcomes including BPD, ROP, NEC, and IVH. Results Of the 250 enrolled VLBW infants, 109 (43.6%) underwent transfusion. Univariate analysis revealed that all short-term outcomes except early-onset sepsis and patent ductus arteriosus were associated with RBC transfusion. In multivariate analysis adjusted for gestational age, birth weight and Apgar score at 1 minute, RBC transfusion was significantly correlated with BPD (odds ratio [OR], 5.42; P<0.001) and NEC (OR, 3.40; P= 0.009). Conclusion RBC transfusion is significantly associated with adverse clinical outcomes such as NEC and BPD in VLBW infants. Careful consideration of the patient's clinical condition and appropriate guidelines is required before administration of RBC transfusions.